Using local authority entrance charges to tackle inequalities in physical activity? A qualitative study of leisure and public health perspectives. (11th September 2017) - Halliday, E; Barr, B; Higgerson, J; Holt, V; Ortiz-Nunez, A; Ward, F
Abstract: Background: Reducing or eliminating entrance charges for the public use of leisure facilities is one potential tool that local authorities (LA) have to reduce inequalities in physical activity (PA). Facility charges are likely to be a greater barrier to access for those who have lower incomes. Methods: Semi-structured 1-to-1 and group interviews were conducted with 33 leisure and public health professionals in seven LAs in north-west England. We investigated how approaches to pricing varied in these settings and rationales influencing decision making. Results: Welfare orientated (e.g. affordability) and commercial drivers (e.g. income generation) featured most prominently across areas. Pricing policies placed less direct focus on public health goals, although tackling inactivity was articulated as part of leisure's role more generally. Local targeting of free/concessionary offers was also defined and implemented differently. Decision makers described navigating competing pressures of providing services for the public 'good' yet remaining financially viable. Conclusion: Many LAs are reviewing the extent of subsidy for facilities or are considering whether to invest public health budgets in leisure. The findings offer evidence of how pricing decisions are made and the approaches adopted in practice as well as the conflicting priorities for decision makers within an austerity context.